2016
DOI: 10.5539/gjhs.v9n4p182
|View full text |Cite
|
Sign up to set email alerts
|

Jordanian Intensive Care Unit Nurses’ Knowledge of Delirium Recognition

Abstract: Introduction: Delirium is a clinical syndrome that negatively affects the outcomes of the intensive care units patients if undetected early and treated well. However, this condition remains under recognized and poorly managed by health care providers including nurses. The objective of this study was to check nurses' knowledge level about delirium recognition. Materials and Methods:This was a cross-sectional study on 176 intensive care units nurses working in four major hospitals in Amman, Jordan. Data were col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…However, nurses have difficulty recognizing delirium in their patients due to the lack of knowledge about delirium evaluation of the patient, risk factors, and interventions to prevent delirium ( Gesin et al, 2012 ; van de Steeg et al, 2014 ). Studies have shown that 75% of the nurses working in the ICU cannot detect delirium in the early period ( Rice et al, 2011 ; AbuRuz, 2017 ), delirium assessment tools are not used effectively, the lack of knowledge about delirium is an essential factor ( Rowley-Conwy, 2018 ), and nurses do not see delirium as a severe syndrome ( Xing et al, 2017 ). Nurses observe patients individually for 24 h and implement their care.…”
Section: Introductionmentioning
confidence: 99%
“…However, nurses have difficulty recognizing delirium in their patients due to the lack of knowledge about delirium evaluation of the patient, risk factors, and interventions to prevent delirium ( Gesin et al, 2012 ; van de Steeg et al, 2014 ). Studies have shown that 75% of the nurses working in the ICU cannot detect delirium in the early period ( Rice et al, 2011 ; AbuRuz, 2017 ), delirium assessment tools are not used effectively, the lack of knowledge about delirium is an essential factor ( Rowley-Conwy, 2018 ), and nurses do not see delirium as a severe syndrome ( Xing et al, 2017 ). Nurses observe patients individually for 24 h and implement their care.…”
Section: Introductionmentioning
confidence: 99%
“…[11] It is recommended to conduct a further study or a focus group discussion to explore why ICU nurses have difficulties in implementing this tool. These results are supported by AbuRuz [18] who stated that around half of the staff reported that they face difficulty in assessing a delirious patient. These findings were in line with Alharbi [13] who noted in her study that 100% of nurses agreed that they were not able to complete a delirium assessment for a sedated patient and they felt that they were not required to screen for ICU delirium, and doctors are the ones responsible for completing a delirium assessment.…”
Section: Discussionmentioning
confidence: 53%
“…*Score for perception: Poor (1-10), Moderate(11)(12)(13)(14)(15)(16)(17)(18)(19)(20), Good(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). *Range: 10-26 *Mean ± SD: 19.27±3 21.…”
mentioning
confidence: 99%